406 Assessing Correlations Between NASS Patient Satisfaction Index and Patient-Reported Outcomes (PROs) at 3-month, 12-month, and 24-month Timepoints in Patients Undergoing Cervical Spine Surgery Using the QOD Registry. (April 2023) - Zaki, Mark M.; Joshi, Rushikesh Sanjeev; Linzey, Joseph Raynor; Strong, Michael J.; Yee, Timothy Joseph; Saadeh, Yamaan S.; Upadhyaya, Cheerag D.; Coric, Domagoj; Potts, Eric A.; Bisson, Erica Fay Randy; Turner, Jay D.; Knightly, Jack; et al.
Abstract : INTRODUCTION: In value-based healthcare, measuring appropriate outcomes is essential to accurately determine value. Tracked outcomes should reflect the desires of patients undergoing surgical interventions. METHODS: The Quality Outcomes Database (QOD), a prospectively collected multi-institutional database, was used to analyze North American Spine Society (NASS) satisfaction, Neck Disability Index (NDI), Visual analog scale for neck pain (NP-VAS) and arm pain (AP- VAS), EuroQoL-Visual Analog Scale (EQ-VAS), and modified Japanese Orthopedic Association (mJOA) at 3, 12, and 24-month follow up. RESULTS: 1141 patients were surgically treated (anterior approach n = 785, 69%; posterior approach n=356, 31%) for cervical spondylotic myelopathy. Average demographics were 60.5 years old, 52.6% male, 92.4% non-Hispanic, BMI 30.2, and length of stay 2.1 days. At 3 month follow up, satisfaction was positively correlated with NP-VAS (R = 0.298, p<.001), AP-VAS (R = 0.315, p < .001), NDI (R = 0.362, p <.001), and negatively correlated with EQ-VAS (R = -0.294, p<.001) and mJOA (R = -0.287, p < .001). At 12 month follow up, satisfaction was positively correlated with NP-VAS (R = 0.442, p<.001), AP-VAS (R = 0.384, p< .001), NDI (R = 0.459, p < .001), and negatively correlated with EQ-VAS (R = -0.357, p<.001) and mJOA (R = -0.363, p <.001). At 24 month follow up, satisfaction was positively correlated with NP-VAS (R = 0.490, p<.001), AP-VAS (R = 0.358, p < .001), NDI (R = 0.491, p < .001), and negatively correlated with EQ-VAS (R= -0.310, p<.001) and mJOA (R= -0.378, p <.001). CONCLUSIONS: NDI was most correlated with satisfaction at 3, 12 and 24-month follow up. mJOA was least correlated with satisfaction at 3 month follow up, whereas EQ-VAS was the least correlated with satisfaction at 12 and 24-month follow up. These findings may better guide outcome selection in patient follow up and help clinicians appropriately counsel patients on expected outcomes.